Penerapan Inovasi Teknologi dan Digital Marketing pada Industri Tahu dan Tempe Khas Bandungan Kab. Semarang - Prananta, Widya; Bintari, Siti Harnina; Wicaksono, Dimas; Rachmadi, Moch Faizal (Universitas Mataram, 2025)
Tofu and tempeh are popular and affordable sources of plant-based protein. They also play a vital role in meeting the food needs of the Indonesian people. Besides containing plant-based protein, tofu and tempeh are also rich in fiber, calcium, iron, and sodium. Furthermore, these soybean products contain prebiotics that can help improve digestive health, isoflavones to lower cholesterol levels, and saponins to protect heart health. The various nutritional contents of soybean products, such as tofu and tempeh, must be optimized. One of the tofu and tempeh producers in Central Java is the